Partisipasi Masyarakat dalam Pengawasan Dana Desa di Desa Gawu-Gawu Bouso Kecamatan Gunungsitoli Utara - Hasmarini Ariestin Waruwu; Erika Revida; Muryanto Amin (Universitas Medan Area, 2023)
The purpose of this study was to analyze community participation in the supervision of village funds and analyze the supporting and inhibiting factors of community participation in the supervision of village funds. The research method used is descriptive with a qualitative approach. The informants in this study were the Headman, Secretary, (BPD), RT, RW, and the Community. The results of this study indicate that community participation in monitoring village funds in Gawu-Gawu Bouso village is still very low or less than optimal. The supporting factor is the awareness or willingness of the community to participate in development activities. While the inhibiting factors are the low quality of education, low income levels, and limited employment opportunities in rural areas.